Levels of satisfaction and service usage of a learning commons as correlates of mathematics achievement and mathematics attitude - LYZA MARIE, LUCHICO (Archīum Ateneo, 2015)
Learning commons as a recent trend in academic libraries includes traditional and technological resources, as well as the advantage of involvement of faculty in the academic achievement of the students. Similar to a learning commons but on a smaller scale